Tailoring nano-sized electron-doped superconductors: The impact of sintering temperatures on particle size and crystal structure - S. H. Hindiyati; S. Winarsih; Y. Maryati; R. Pratama; Risdiana Risdiana (AIP Advances)
Nanoparticles are reported to have magnetic and electrical properties. In this context, materials with nanoparticle size are synthesized using various methods, such as sol–gel, solid state, and co-precipitation methods. The sol–gel method offers superior control over particle growth, allowing for the synthesis of nanoparticles smaller than those used in conventional solid-state methods. Therefore, this research aims to synthesize electron-doped superconducting nanoparticles Eu1.86Ce0.14CuO4+α‒δ (ECCO) using the sol–gel method with sintering temperatures ranging from 800 to 1050 °C. X-ray fluorescence (XRF) and diffraction (XRD) confirmed the stoichiometric consistency and the presence of T crystal structure in all samples, respectively. Field emission scanning electron microscopy (FE-SEM) reported a direct correlation between sintering temperature and particle size of 131–172 nm. The result shows that sintering temperature plays a crucial role in controlling nanoparticle size, offering insights for optimizing the properties of electron-doped superconductors.